Wideband Waveguide-to-Microstrip Transition for mm-Wave Applications - Andrey V. Mozharovskiy; Oleg V. Soykin; Aleksey A. Artemenko; Roman O. Maslennikov; Irina B. Vendik (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Increased data rate in modern communication systems can be achieved by raising the operational frequency to millimeter wave range where wide transmission bands are available. In millimeter wave communication systems, the passive components of the antenna feeding system, which are based on hollow metal waveguides, and active elements of the radiofrequency circuit, which have an interface constructed on planar printed circuit boards (PCB) are interconnected using waveguide-to-microstrip transition.Aim. To design and investigate a high-performance wideband and low loss waveguide-to-microstrip transition dedicated to the 60 GHz frequency range applications that can provide effective transmission of signals between the active components of the radiofrequency circuit and the passive components of the antenna feeding systemMaterials and methods. Full-wave electromagnetic simulations in the CST Microwave Studio software were used to estimate the impact of the substrate material and metal foil on the characteristics of printed structures and to calculate the waveguide-to-microstrip transition characteristics. The results were confirmed via experimental investigation of fabricated wideband transition samples using a vector network analyzer Results. The probe-type transition consist of a PCB fixed between a standard WR-15 waveguide and a back-short with a simple structure and the same cross-section. The proposed transition also includes two through-holes on the PCB in the center of the transition area on either side of the probe. A significant part of the lossy PCB dielectric is removed from that area, thus providing wideband and low-loss performance of the transition without any additional matching elements. The design of the transition was adapted for implementation on the PCBs made of two popular dielectric materials RO4350B and RT/Duroid 5880. The results of full-wave simulation and experimental investigation of the designed waveguide to microstrip transition are presented. The transmission bandwidth for reflection coefficient S11 < –10 dB is in excess of 50…70 GHz. The measured insertion loss for a single transition is 0.4 and 0.7 dB relatively for transitions based on RO4350B and RT/Duroid 5880.Conclusion. The proposed method of insertion loss reduction in the waveguide-to-microstrip transition provides effective operation due to reduction of the dielectric substrate portion in the transition region for various high-frequency PCB materials. The designed waveguide-to -microstrip transition can be considered as an effective solution for interconnection between the waveguide and microstrip elements of the various millimeter-wave devices dedicated for the 60 GHz frequency range applications.